2020
DOI: 10.31580/apss.v6i2.1315
|View full text |Cite
|
Sign up to set email alerts
|

Abstract ID : AIMC-2020-EBM-529 Do Students in Engineering Universities behave like Employees/Co-workers? Exploring Relationship of Islamic Work Ethics and Organizational Behaviors among Engineering Students.

Abstract: This study explores the relationships between Islamic Work Ethics (IWE), workaholism (WA) and positive and negative Organizational Behaviors (OBs) amongst Engineering Students. Most of the researchers have studied OBs and ethics among faculty or administrative staff in universities. Study of these behaviors among students is a novel area of research. This study proposes an integrated framework of Islamic Work Ethics (IWE), Organizational Citizenship Behavior (OCB), Constructive and Destructive Deviant Behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In Islamic countries like Pakistan, where approximately 97% of the population is Muslim, the WE followed is IWE, which is a part of the individuals' education/grooming [53]. Many researchers have found that IWE has significant positive or negative relationships with individuals' positive and negative behaviors towards colleagues/organizations [57,58]. Scholars have found that behaviors and attitudes like unity, justice, the need for balance, and knowledge-seeking is promoted by IWE [58].…”
Section: Indirect Effects Of We On Productivity Through Mediators (Obmentioning
confidence: 99%
“…In Islamic countries like Pakistan, where approximately 97% of the population is Muslim, the WE followed is IWE, which is a part of the individuals' education/grooming [53]. Many researchers have found that IWE has significant positive or negative relationships with individuals' positive and negative behaviors towards colleagues/organizations [57,58]. Scholars have found that behaviors and attitudes like unity, justice, the need for balance, and knowledge-seeking is promoted by IWE [58].…”
Section: Indirect Effects Of We On Productivity Through Mediators (Obmentioning
confidence: 99%
“…There are many works that prove the positive relationship between IWEs and employee behaviours and organizational success. This includes Amilin et al (2018), Zin et al (2018), Khurram et al (2020), Sattar et al (2020) and Romi and Ahman (2020). By analysing their works, IWEs can also be said to be related to the employee behaviour and professionalism, where if the employee practices IWEs, they will improve their behaviour and also professionalism.…”
Section: Empirical Studies On Customer Satisfaction and Employee Professionalismmentioning
confidence: 99%